Evolution of explosive strength and maximum oxygen consumption in high and medium level basketball players - Mondoni, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Basketball players` performance strongly depends on explosive strength and maximal oxygen consumption (VO2-MAX) [1]. Some authors have found that these assets proportionally increase with players` qualification [2].The aim of this research was to monitor the improvements due to training programs in two different qualification level players: medium and high. A test of explosive strength and the estimation of VO2-MAX were considered. Methods: 43 basketball players were assigned to 2 groups. Group A consisted of 22 high level athletes (1st and 2nd division, 27.2±5.2 y, 1.94±0.08 m; 88.3±8.90 kg, BMI 23.4±1.5). Group B was made up of 21 medium level players (3rd and 4th division, 23.9±4.6 y, 1.92±0.06 m; 88.5±8.90 kg, BMI 23.8±1.5). Within each group, all subjects performed the same program of technical and physical conditioning (8 training sessions a week for A, 3 for B). The explosive strength and VO2-MAX of each athlete were measured at the beginning (t0) and at the half (t1) of the competitive season. The explosive force was assessed by measuring the height (H) of the jump (Optojump, Microgate, Bolzano, Italy) in countermovement vertical jump test (CMJ). Each athlete performed 3 trials and their best attempt was taken into account. The VO2-MAX was indirectly estimated following the protocol proposed by Leger et al [3]. Significant differences between pre and post tests within groups were evaluated through Wilcoxon tests (P<0.05). The comparison between A and B concerning the increase of H and VO2-MAX was performed by using the Mann-Whitney test (P<0.05). Results: Group A had a significant increase of both H and VO2-MAX, who passed respectively from (median and IQR) 48.0 (14.7) cm and 56.9 (3.5) ml/min/kg in t0, to 49.5 (13.4) cm and 60.5 (4.6) ml/min/kg in t1. Group B did not evidence significant changes between the pre (48.3 (4.3) m and 56.3 (3.6) ml/min/kg) and post (48.2 (7.4) m and 55.4 (4.8) ml/min/kg) session. Discussion: Results suggested that in high level basketball players the number of 8 training section during the week appears effective for increasing the performance of CMJ and VO2-MAX. In contrast, training programs of group B were not enough to enhance explosive force and maximal oxygen consumption. This may be related to the lack of physical conditioning within weekly workouts.